Reassessing Electoral Design and Constitutional Consistency in Indonesia - Febrianti Puspitasari; Hananto Widodo; Alfalah Fadhilah Fiisabilillah (NOVUM : JURNAL HUKUM, 2025)
This study is motivated by the Constitutional Court's paradigm shift in interpreting the design of general elections in Indonesia, from initially promoting simultaneous elections through Decision Number 14/PUU-XI/2013 to emphasizing the separation between national elections and regional head elections. The focus of this research is the legal implications of this separation on the presidential system of government as well as budget efficiency and the effectiveness of government administration within the framework of the Unitary State of the Republic of Indonesia. The research uses a normative legal method with a legislative, conceptual, and case approach, through qualitative analysis of the 1945 Constitution, Constitutional Court decisions, as well as scientific literature and journals based on the theories of Democracy, Authority, the Presidential System, the Unitary State, and the Open Legal Policy doctrine. The results of the study show that Constitutional Court Decision Number 135/PUU-XXII/2024 reflects the Court's inconsistency in applying the Open Legal Policy doctrine, which has an impact on disrupting the synchronization of national policies, increasing the budget burden, and the potential for weakening government stability, so that it is not yet fully in line with the spirit of constitutional integration and effective governance.